Pengembangan Teknologi Audio-Visual dalam Pembelajaran Bahasa Arab - Baiq Raudatussolihah (Education and Learning Journal, 2022)
This study aims to explain the types of audio-visual and their advantages and disadvantages in learning Arabic, and the use of audio-visual technology in learning Arabic. The method used in this research is qualitative research with a descriptive approach and its implementation is through library research and literature review. Audio-visual technology is a medium that educators can use in learning Arabic that is easy to understand and fun. Moreover, it is supported by technological developments that can be used as audio-visual media in the development of Arabic learning. Educators can also direct students to visit internet sites that discuss Arabic studies according to the theme and level of students.